TECHNIQUE OF ASSESSMENT OF EXPEDIENCY OF APPLICATION OF OUTSOURCING - Farkhoutdinov, Ilnour I.; Isavnin, Alexey G. (Gênero & Direito, 2019)
One of the main criteria of successful application of production outsourcing is competent definition of degree of expediency of use of this tool at the enterprise. Reasonable combination of outsourcing and insourcing where management of them is constructed on in advance defined accurate principles, and identification of exact borders of outsourcing are pledge of effective application of this model of management at the enterprise. Therefore there is a need for a reliable technique which would allow to define competently the product components which are subject to transfer to outsourcing. The purpose of this work is development of a technique of an assessment of expediency of application of production outsourcing at the enterprise, and also definition of major factors of adoption of the administrative decision on use of this tool.The offered technique is based on matrix approach.In the real work as authors the technique of an assessment of expediency of application of production outsourcing at the enterprise is offered.Results of the real work can be of interest to heads of the large industrial enterprises, and also can be useful to further scientific researches in the field of sourcing.The offered technique allows to define competently the product components which are subject to transfer to outsourcing